2011
DOI: 10.1155/2011/426127
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Uterine Rupture Causing Fetal Expulsion into the Abdominal Cavity: A Rare Case of Neonatal Survival

Abstract: Introduction. Uterine rupture is a potentially catastrophic complication of vaginal birth after caesarean section. We describe the sixth case of posterior uterine rupture, with intact lower segment scar, and the first neonatal survival after expulsion into the abdominal cavity with posterior rupture. Case Presentation. A multiparous woman underwent prostaglandin induction of labour for postmaturity, after one previous caesarean section. Emergency caesarean section for bradycardia revealed a complete posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Rupture of an unscarred uterus occurs rarely with an estimated occurrence of 1 in 17,000-20,000 deliveries. In India, Pagi et al (1995) found that the most common group was spontaneous (63.69%) followed by scar rupture(22%) and traumatic(14.8%).Very similar figures were also given earlier by Dhar (1989) from Srinagar, India [2]. Clinical signs of uterine rupture during pregnancy are nonspecific, and very variable.…”
Section: Discussionmentioning
confidence: 62%
“…Rupture of an unscarred uterus occurs rarely with an estimated occurrence of 1 in 17,000-20,000 deliveries. In India, Pagi et al (1995) found that the most common group was spontaneous (63.69%) followed by scar rupture(22%) and traumatic(14.8%).Very similar figures were also given earlier by Dhar (1989) from Srinagar, India [2]. Clinical signs of uterine rupture during pregnancy are nonspecific, and very variable.…”
Section: Discussionmentioning
confidence: 62%
“…4 This is similar to sacculation in which the posterior uterine wall softens allowing the posterior uterine wall to swell like an aneurysm allowing growth of the fetus into the abdomen with increased risk of UR.…”
Section: Discussionmentioning
confidence: 98%
“…Rupture of the posterior wall of in women attempting VBAC has also been described, although it's extremely rare. 4 Outcomes of uterine rupture (UR) depend on the time between diagnosis of rupture and delivery. They include fetal and maternal complications.…”
Section: Introductionmentioning
confidence: 99%
“…Rupture of the unscarred uterus varies more hazardless foetomaternal risk compared to scarred uterus. (2) Even though the mode of presentation was similar for patients with or without CS history, instability, deterioration of vital parameters and vaginal bleeding after labour must remind likelihood of UR.…”
Section: Discussionmentioning
confidence: 99%
“…A complete UR involves the entire uterine wall leading to a direct connection between the peritoneal space and the uterine cavity, whereas a cover of visceral, peritoneum of the broad ligament is left over the uterus in case of an incomplete UR. (2) In women with two or more prior caesareans, the rate of rupture rises as high as 3.9 percent. (7) The underlying factors for UR include a poor referral system, non-attendance to antenatal care, delay in seeking medical care and delay of essential intervention.…”
Section: Discussionmentioning
confidence: 99%